Mouth Breathing, Head Posture, and Prevalence of Adenoid Facies in Patients with Upper Respiratory Tract Obstruction - Purwanegara, Miesje Karmiati; Sutrisna, Bambang (UI Scholars Hub, 2018)
Frequent upper respiratory tract infections and allergic reactions may cause upper respiratory tract obstruction (OURT). Mouth breathing (MB) occurs in individuals with nasal breathing problems. A person with MB will raise his head higher; thus, MB is a risk factor for head posture (HP) deviation. Children with MB during growth and development may exhibit dentocraniofacial (DCF) deviation. Objective: To evaluate the prevalence of MB, HP, and DCF deviation in OURT patients to know risk factors of HP deviation, morphological aberrations of DCF and DCF deviation growth and development. Methods: This cross-sectional study included 285 OURT subjects aged 9–15 years. Data obtained from cephalometric analysis, physical examination, and questionnaires were analyzed. Results: Of 285 OURT subjects, 80.4% showed MB, 44.2% HP deviation, and 66.7% DCF deviation. As risk factors for DCF deviation, MB and HP showed odds ratios of 20.45 and 8.11 and population attributable risks of 87.5% and 59.7%, respectively. Conclusion: The prevalence of MB and DCF deviation in OURT patients is high, but that of HP deviation is generally comparable. MB and deviated HP are risk factors for DCF deviation growth and development.